Adaptation to nonlinear frequency compression in normal-hearing adults: A comparison of training approaches. (October 2014) - Dickinson, Ann-Marie; Baker, Richard; Siciliano, Catherine; Munro, Kevin J.
Abstract Objective: To identify which training approach, if any, is most effective for improving perception of frequency-compressed speech. Design: A between-subject design using repeated measures. Study sample: Forty young adults with normal hearing were randomly allocated to one of four groups: a training group (sentence or consonant) or a control group (passive exposure or test-only). Test and training material differed in terms of material and speaker. Results: On average, sentence training and passive exposure led to significantly improved sentence recognition (11.0% and 11.7%, respectively) compared with the consonant training group (2.5%) and test-only group (0.4%), whilst, consonant training led to significantly improved consonant recognition (8.8%) compared with the sentence training group (1.9%), passive exposure group (2.8%), and test-only group (0.8%). Conclusions: Sentence training led to improved sentence recognition, whilst consonant training led to improved consonant recognition. This suggests learning transferred between speakers and material but not stimuli. Passive exposure to sentence material led to an improvement in sentence recognition that was equivalent to gains from active training. This suggests that it may be possible to adapt passively to frequency-compressed speech.